Analysis of yam yields using the additive main effects and multiplicative interaction (AMMI) model - Egesi, Chiedozie N.; Asiedu, Robert (2002)
The AMMI model combines regular analysis of variance for additive main effects with principal component analysis for multiplicative structure within the interaction. It also improves the accuracy of crop yield estimates and selects genotypes with highest yields. Despite knowledge of the model, potential yield estimates for yam cultivars as is the case for several other crops, are largely unknown. In this study, the AMMI model was used with the objective of assessing yam genotypes yield, selecting stable genotypes, and investigating G x E effects from trials conducted for two years at five locations in Nigeria. The effects of environments, genotypes and genotype-by-environment interaction (G x E) were highly significant (P<0.001). Within environments, AMMI1 estimates ranked genotypes differently from the unadjusted means, and in six out of nine cases AMMI1 estimates changed the top-yielding entry. The AMMI1 estimation also produced sharper and stratified rankings compared with the unadjusted means. The biplot showed four groupings of genotypes: TDa 93-36 generally low yielding and unstable; TDa 291 and TDa 297, low yielding and moderately stable; TDa 294 and TDa 87/01091 high yielding and stable; TDa 92-2 high yielding but unstable. Yam yields were relatively stable at Ibadan and Jos, while yields obtained at Abuja were unstable across both years. Superior yam selections with specific or broad adaptation were identified by AMMI.